2010
DOI: 10.1111/j.1365-2923.2010.03736.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental challenges, stressors and coping strategies in medical residents: a qualitative analysis of support groups

Abstract: Introduction-Stress and burnout are endemic to post-graduate medical training but little research is available to guide supportive interventions. The identification of longitudinal emotional and developmental coping needs of internal medicine residents could assist in better designing and implementing supportive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 21 publications
3
84
0
1
Order By: Relevance
“…Of the 14 observational studies that were assessed using the NOS (provided as online supplemental material), 2 were rated high quality, 12,13 and 7 were rated as being of moderate quality. 3,9,14,15,17,21,24 Of the 5 RCTs that were assessed using the Jadad scale (TABLE 1), 3 were rated high quality 8,18,19 (score ! 3), and the remaining 2 were rated to be of moderate quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 14 observational studies that were assessed using the NOS (provided as online supplemental material), 2 were rated high quality, 12,13 and 7 were rated as being of moderate quality. 3,9,14,15,17,21,24 Of the 5 RCTs that were assessed using the Jadad scale (TABLE 1), 3 were rated high quality 8,18,19 (score ! 3), and the remaining 2 were rated to be of moderate quality.…”
Section: Resultsmentioning
confidence: 99%
“…Some other interventions to address burnout have been suggested, including supportive interventions for internal medicine residents. 3 Identifying challenges faced by trainees at different levels and across different specialties may assist in improved, effective tailoring of interventions. For example, 1 study found a significant correlation among burnout rates, peer relationships, and interventions aimed at improving peer relationships, which may reduce burnout in resident physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past research has shown the value of peer support and the active role it plays in professional growth and satisfaction. 5 Group sessions would foster camaraderie; encourage honest, judgment-free discussions; and actively combat the feelings of isolation characteristic of depression.…”
mentioning
confidence: 99%